A comprehensive overview of selective and novel fibroblast growth factor receptor inhibitors as a potential anticancer modality - Jain Nem Kumar; Tailang Mukul; Thangavel Neelaveni; Makeen Hafiz A.; Albratty Mohammed; Najmi Asim; Alhazmi Hassan Ahmad; Zoghebi Khalid; Alagusundaram Muthumanickam; Jain Hemant Kumar; Chandrasekaran Balakumar (Acta Pharmaceutica)
The arrival of comprehensive genome sequencing has accelerated the understanding of genetically aberrant advanced cancers and target identification for possible cancer treatment. Fibroblast growth factor receptor (FGFR) gene alterations are frequent findings in various rare and advanced cancers refractive to mainstay chemo-therapy or surgical interventions. Several FGFR inhibitors have been developed for addressing these genetically altered FGFR-harboring malignancies, and some have performed well in clinical trials. In contrast, others are still being investigated in different phases of clinical trials. FDA has approved four anticancer agents such as erdafitinib, pemigatinib, infigratinib, and futibatinib, for clinical use in oncogenic FGFR-driven malignancies. These include cholangiocarcinoma, urothelial carcinoma, and myeloid/lymphoid malignancies. Pemigatinib is the only FGFR inhibitor globally approved (USA, EU, and Japan) and available as a targeted therapy for two types of cancer, including FGFR2 fusion or other rearrangements harboring cholangiocarcinoma and relapsed/refractory myeloid/lymphoid neoplasms with FGFR1 rearrangements. Myeloid/lymphoid neoplasm is the latest area of application added to the therapeutic armamentarium of FGFR inhibitors. Furthermore, futibatinib is the first-in-class covalent or irreversible pan-FGFR inhibitor that has received FDA approval for locally advanced or metastatic intrahepatic cholangiocarcinoma harboring FGFR2 gene aberrations. This review highlights the current clinical progress concerning the safety and efficacy of all the approved FGFR-TKIs (tyrosine kinase inhibitors) and their ongoing investigations in clinical trials for other oncogenic FGFR-driven malignancies.